Synthesis, structures and catalytic activity of cyclometalated rhenium complexes. Issue 28 (17th March 2017) - Sun, Ruichen; Wang, Tian; Zhang, Shaowei; Chu, Xiaodan; Zhu, Bolin
Abstract : Several five-membered cyclometalated rhenium complexes (1–5 ) were synthesized, and their photocatalytic activity on direct arylation of arenes with aryl halides was examined. Abstract : Thermal reactions of aryl-substituted phosphines or phosphinites with Re2 (CO)10 in chlorobenzene resulted in the corresponding five-membered cyclometalated rhenium complexes (1–5 ) via an intramolecular activation of the C(sp 2 )–H or C(sp 3 )–H bond. The only exception occurred in the case of (1-naphthyl)diisopropylphosphinite, which gave a diphosphinite-substituted dinuclear rhenium complex6 . Competition reaction indicated that the aromatic C(sp 2 )–H bond is more likely to be activated than the C(sp 3 )–H bond under the same conditions. Photolysis of1 or2 in CHX3 led to the cleavage of the Re–C σ bond to yield corresponding phosphine-substituted tetracarbonyl rhenium halides7–10 . Complex1 reacted with CF3 COOH in CH2 Cl2 to give addition product11 . Photolysis of cyclorhenated complexes1–3 with a series of aryl halides in benzene resulted in the stoichiometric formation of biphenyl, together with corresponding phosphine-substituted tetracarbonyl rhenium halides (7, 9, 10, 12, and13 ). When base was introduced into the above reaction, a catalytic system was established. Under optimized conditions, complex1 provided moderate yield of biphenyl in a couple of hours at a [Re] : substrate ratio of 1 : 200. Molecular structures of complexes1, 6, 9, and11 were determined by X-ray diffraction.